The mental health experiences of ethnic minorities in the UK during the Coronavirus pandemic: A qualitative exploration - Van Bortel, Tine; Lombardo, Chiara; Guo, Lijia; Solomon, Susan; Martin, Steven; Hughes, Kate; Weeks, Lauren; Crepaz-Keay, David; McDaid, Shari; Chantler, Oliver; Thorpe, Lucy; Morton, Alec; et al. (Frontiers in Public Health, 2022)
Worldwide, the Coronavirus pandemic has a major impact on people’s health, lives and livelihoods. However, this impact has not been felt equally across various population groups. People from ethnic minority backgrounds in the UK have been more adversely affected by the pandemic, especially in terms of their physical health. Their mental health, on the other hand, has received less attention. This study aimed to explore the mental health experiences of UK adults from ethnic minorities during the Coronavirus pandemic. This work forms part of our wider long-term UK study ‘Mental Health in the Pandemic’. We conducted an exploratory qualitative study, interviewing people from ethnic minority communities across the UK. Interviews took place online via MS-Teams or Zoom. In-depth interviews were conducted with 15 women, 14 men and 1 non-binary person from ethnic minority backgrounds, aged between 18-65 (mean age = 40). The qualitative data analysis yielded seven overarching themes: (1) pandemic-specific experiences; (2) coping mechanisms; (3) media issues; (4) attitudes towards vaccination; (5) suggestions for support in moving forward; (6) best and worst experiences during pandemic and lockdowns; (7) biggest areas of change in personal life. Generally, participants’ mental health experiences varied with some not being affected by the pandemic in a way related to their ethnicity, some sharing positive experiences and coping strategies (exercising more, spending more time with family, community cohesion), and some expressing negative experiences (eating or drinking more, feeling more isolated, or even racism and abuse, especially towards Asian communities). Concerns were raised around trust issues in relation to the media, the inadequate representation of ethnic minorities, and spread of fake news especially on social media. Attitudes towards vaccinations varied too, with some people more willing to have the vaccine than others. This study’s findings highlight the diversity in the pandemic mental health experiences of ethnic minorities in the UK and has implications for policy, practice and further research. To enable moving forward beyond the pandemic, our study surfaced the need for culturally appropriate mental health support, financial support (as key mental health determinant), accurate media representation, and clear communication from the Governments of the UK.